Expiry of medicine in public health facilities of Arsi Zone, Oromia Regional State, Ethiopia: a quantitative and qualitative study - Jemal Tura, Abdurazak; Doyo Dalecha, Debesa; Yasir, Mohd; Aman Ketebo, Tahir; Noorulla, KM (Current Issues in Pharmacy and Medical Sciences, 2022)
Medicines are one of the critical elements of a well-functioning healthcare system, but their expiry remains one of the significant challenges in the healthcare sector. This study aims in assessing the extent of the issue and identifying the expired medicine types and their underlying causes in some selected public health facilities of Arsi Zone, Oromia Regional State, Ethiopia. This study is a mixed-method, which includes both quantitative and qualitative components. The quantitative research was undertaken by retrospective data extraction of recorded medicines as expired for the specified period. At the same time, the qualitative part is a facility-based cross-sectional survey study with self-administered questionnaires and semi-structured in-depth interviews engaging the health professionals of study facilities to explore the reasons for the expiration of medicines. Fifteen health facilities were selected from the study zone. The total monetary value of expired medicines in the studied health facilities during 2017-2019 was 185,938.86 USD. In the same period, all study facilities received medicines worth 2,425,882.64 USD, resulting in an expiry rate of 7.66%. The top classes of wasted medicines through expiry in terms of value were anti-infectives (35.51%) and medicines for central nervous system (CNS) disorders (20.48%). In comparison, by dosage forms, nearly half were solid dosage forms (48.81%), followed by liquid dosage forms (41.82%). Delivery of near expiry date medicines by Ethiopia’s Pharmaceuticals Supply Agency (PSA), lack of a system to exchange nearly expired medicines between facilities, and presence of overstocked medicines due to improper forecasting of need were the common perceived factors contributing to the expiry of medicines. Thus, the Policymakers should make decisions to reduce the contributing factors of medicines expiry to reduce wastage of medicines and promote appropriate utilization of finite resources.